Effectiveness of LOF Mixture from Banana Peel with Rice Water and Goat Manure on the Growth of Hydroponic Brassica juncea - Luthfiyah, Annisa Ulfa; An Nisaa, Ranti; Setyaningsih, Maryanti; Anugrah, Devi (LenteraBio : Berkala Ilmiah Biologi, 2024)
Liquid organic fertilizer is a nutrient made from organic materials from animal and plant waste. The use of banana peels, rice water, or goat manure as LOFs was reported to affect the growth of mustard greens and several types of vegetables. The use of LOF made from a mixture of these three organic ingredients has never been done to see its effect on the growth of mustard greens. Completely randomized design was performed with four treatments, P0 = control, P2 = 2% LOF, P3 = 5% LOF, and P4 = 7.5% LOF, with 5 repetitions. Parameters of plant were observed until 42 DAP. The results of the ANOVA test for plant height calculation F count = 7.62; number of leaves F count = 4.5; wet weight F count = 1.33; and dry weight F count = 2.54. Based on this test, it can be seen that the LOF of the mixture from banana peels, rice water, and goat manure only affected plant height, while the number of leaves, wet weight, and dry weight had no effect. The nutritional content of POC is still less than that required by mustard greens, this POC does not have a positive impact.